The Effectiveness of Mindfulness-Based Cognitive Therapy for Major Depressive Disorder and Relapse Prevention - Li, Yifang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Due to the prevalence and severity of Major Depressive Disorder (MDD), it is essential to examine the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) when treating and preventing the recurrence of MDD. This paper evaluated recent research in this area. First, this article described the importance of research on MDD, which has led to considering MBCT techniques for treating MDD. In addition, this article presented previous literature which explored the symptoms and causes of MDD, as well as the mechanisms and theories of mindfulness training and Cognitive Behavioral Therapy (CBT). Moreover, the paper reviewed recent findings in this area and compared the overall effectiveness of MBCT, Active Control Condition (ACC), and medical therapy when treating MDD. Plus, this paper identified the core components of MBCT, including self-compassion cultivation, meditation training, attentional bias improvement, and meta-cognitive skill enhancement. Finally, this paper also proposed that future research should involve large and diverse samples, longer-term studies, subgroup analyses, and qualitative research to understand MBCT’s effectiveness and applications more comprehensively.